Agar extraction process for Gracilaria cliftonii (Withell, Miller and Kraft, 1994) - Kumar, Vivek; Fotedar, Ravi (Elsevier, 2009)
Agar extraction process was developed for Gracilaria cliftonii by investigating the effects of various extraction variables and alkali treatments on agar yield and properties. The tested variables were soaking time, soaking temperature, seaweed to water ratio of, extraction temperatures and extraction time. Alkali treatments were carried out in alkali concentrations of 1%, 2%, 3% and 5% in a water bath at 60, 70 and 80 C prior to agar extraction. The results showed that agar yield was significantly affected by all the tested variables. The agar yield was maximised when extraction process was carried out with 1 h soaking time at 30 C with seaweed to water ratio of 1:150 and extracted for 3 h at 100 C. The alkali-temperature combinations significantly influenced agar yield and properties. Irrespective of temperature, alkali treatments at 3% and 5% significantly increased the gel strength.